2021
DOI: 10.3390/ijms22073414
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Enrichment Enhances Cav 2.1 Channel-Mediated Presynaptic Plasticity in Hypoxic–Ischemic Encephalopathy

Abstract: Hypoxic–ischemic encephalopathy (HIE) is a devastating neonatal brain condition caused by lack of oxygen and limited blood flow. Environmental enrichment (EE) is a classic paradigm with a complex stimulation of physical, cognitive, and social components. EE can exert neuroplasticity and neuroprotective effects in immature brains. However, the exact mechanism of EE on the chronic condition of HIE remains unclear. HIE was induced by a permanent ligation of the right carotid artery, followed by an 8% O2 hypoxic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 83 publications
(94 reference statements)
0
3
0
Order By: Relevance
“…In healthy individuals, we expect that grip strength and force profile should be highly correlated. Indeed, peak grip strength and cumulative force profile are often used interchangeably to report about muscle 12 , 13 or neural physiology 14 16 . However, it is appreciated that muscle impairment likely differs depending upon the disease context.…”
Section: Introductionmentioning
confidence: 99%
“…In healthy individuals, we expect that grip strength and force profile should be highly correlated. Indeed, peak grip strength and cumulative force profile are often used interchangeably to report about muscle 12 , 13 or neural physiology 14 16 . However, it is appreciated that muscle impairment likely differs depending upon the disease context.…”
Section: Introductionmentioning
confidence: 99%
“…When NAAG levels increased 12–24 h after HI, so did mGluR3 expression, and NAAG was positively correlated with mGluR3, implying that NAAG binding to mGluR3 increased and downstream molecular pathways were activated during this period. The main function of voltage-sensitive Ca 2+ channels is to control Ca 2+ entry into the cell to influence the vesicular neurotransmitter release and to bind to and regulate Ca 2+ -dependent neurotransmitter release from the cytoplasmic domain of the transmembrane polypeptide of syph [ 43 , 44 ]. Therefore, this study further confirmed the effect of NAAG on syph and SVs.…”
Section: Discussionmentioning
confidence: 99%
“…Speci cally, EE has been found to improve recognition memory in animal models of normal aging and disease by stimulating synaptic plasticity via increased numbers of dendritic spines and enhanced synaptic function [16][17][18]. EE is also known to have an effect on neuronal activity through regulating the expression of ion channels and synaptic proteins of many brain areas including the PFC [19], hippocampus [20,21] and NAc [22]. Thus, it is not surprising that EE may exert neuroplasticity and neuroprotective effects in adult mice following SI.…”
Section: Introductionmentioning
confidence: 99%